A veratraldehyde-appended organosilicon probe and its hybrid silica nanoparticles as a dual chemosensor for colorimetric and fluorimetric detection of Cu2+ and Fe3+ ions. (7th December 2021) - Singh, Gurjaspreet; Kaur, Jashan Deep; Pawan,; Sushma,; Priyanka,; Satija, Pinky; Singh, K. N.; Esteban, María Angeles; Espinosa-Ruíz, Cristóbal
Abstract : Schiff bases of veratraldehyde based organosilatranes have been synthesized. The colorimetric and fluorimetric detection of 3a and its hybrid silica nanoparticles (V-NPs) revealed significant sensorial ability only towards Cu 2+ and Fe 3+ ions. Abstract : This article highlights the design and synthesis of the Schiff bases of veratraldehyde-based organosilatranes and organosilocanes (3a–3c ), which were meticulously characterized with the aid of nuclear magnetic resonance (NMR, 1 H and 13 C) and mass spectroscopy techniques. Moreover, compound 3a was fabricated over silica nanoparticles by a one-pot method, which was authenticated by infrared (IR) spectroscopy, X-ray diffractometry (XRD), energy dispersive X-ray spectroscopy (EDX), thermogravimetric analysis (TGA), and field emission scanning electron microscopy (FE-SEM) analysis. The colorimetric and fluorimetric detection of 3a and its hybrid silica nanoparticles (V-NPs) revealed their significant sensing ability towards Cu 2+ and Fe 3+ ions over other relevant competitive metal ions. Interestingly, the binding of sensor 3a and the V-NPs with Cu 2+ and Fe 3+ ions manifested an instant color change from yellow to light green and colorless, respectively, in daylight, which is detectable by the naked-eye, and a fluorescence turn-off response under UV light. The results demonstrate that the organic–inorganic nanohybrids exhibited better sensitivity, greater affinity and lower limit of detection leading to better response time than the parent 3a towards Cu 2+ and Fe 3+ ions in the optimum physiological pH range. A computational analysis using the DFT approach was performed to gain insight into the complexation mode of 3a with Cu 2+ and Fe 3+ ions. In addition to this, anti-oxidant properties were also investigated for compounds 3a–3c . Altogether, these findings pave the way for the design and synthesis of dual metal ion sensors.